The Effect of Astragaloside on Pacemaker Current and the Cytoskeleton in Rabbit Sinoatrial Node Cells Under the Ischemia and Reperfusion Condition - Liu, Ruxiu; Li, Jie; Liu, Yu; Peng, Jie; Guan, Xuanke (Frontiers in Pharmacology, 2018)
Objective: We investigated the role of astragaloside in the treatment of sick sinus syndrome (SSS). Methods: Neonatal New Zealand rabbits were selected for the study. Rabbit sinoatrial node (SAN) cells were isolated by the method of dual enzymatic digestion and differential adherence. The injury model was prepared through simulated ischemia and reperfusion (I/R), and changes in the pacemaker current (If) were recorded using the whole-cell patch-clamp technique. The proteins F-actin and vinculin were examined between various groups of SAN cells using a microplate reader and laser scanning confocal microscopy. The mRNA level and protein expression of hyperpolarization-activated cyclic nucleotide gated potassium channel 4 (HCN4) were assessed by q-PCR and western blot method. Results: The peak current density of If was decreased to -19.64±2.14 pA/pF in SAN cells after simulated I/R, and the difference was highly significant (P<0.01). Following simulated I/R, 100, 200, or 300 μmol L-1 astragaloside was added to the extracellular solution of SAN cells; the peak current density of the If increased to -30.43±1.98 pA/pF, -34.83±1.6 pA/pF, and -52.72±1.7 pA/pF, respectively (P<0.01). Adding 100 μmol L-1 astragaloside to normal SAN cells also led to an enhanced peak current density of the If (P<0.05). In a concentration-dependent manner, especially at 300 μmol/L, astragaloside was capable of increasing the expression of HCN4 and protecting the structural stability of F-actin and vinculin in the damaged SAN cells. Conclusion: We estimated that astragaloside could shorten the action potential duration 20 (APD20) and APD50 in damaged SAN cells of neonatal rabbits, thereby increasing the expression of HCN4 and the If current density in damaged SAN cells of neonatal rabbits in a voltage-dependent manner, accelerating the steady-state activation of the If channels, and protecting damaged cytoskeleton. Keywords: sinoatrial node cells of neonatal rabbits; patch clamp; pacemaker current; astragaloside; ischemia/reperfusion